Derevnya na beregu Seny - Alfred, Sisley (Изогиз (Izogiz), 1955)
Artwork; landscape of village on a river bank 1955 reproduction of 1877 painting by A. Sisley. Original title: Деревня на берегу Sены. Suggested translation: Village on the banks of the Seine PO-0318